Virtual Reality (VR) in Superior Education Distance Learning: A Systematic Literature Review - Christian, Bernuy; Salvador, Chumbe; Christian, Garcia (JOIV : International Journal on Informatics Visualization, 2021)
Virtual Reality (VR) is one of the most popular contemporary technologies and it is widely used in the videogame industry, nonetheless, this does not restrict its use in other areas of science, such as medicine or education. Due to the large commotion caused by the appearance of Covid-19, long distance virtual education technologies (e-learning) are being used. With this context, virtual reality is the focus of this study, which had the objective of understanding the work done in superior education at a distance, through the use of VR, by doing a systematic literature review (SLR; LSR in Spanish). The results reveal that the use of VR in education can improve the experience, motivation and the comprehension of abstract concepts for the students, offering them an immersive environment in which they can interact and achieve effective learning. It was concluded that the works that were reviewed regarding the topic evidence a strong growth in the application of VR in education, which in their majority, employ experimental comparative methods between groups of students which use VR when compared to others who use the traditional method.